Second language learners’ (English majors) writing apprehension and their use of online applications for writing - Mat Daud, Nuraihan; Mat Daud, Nor Shidrah; Simpson, Jantima (E.L.E. Publishing, 2020)
This study reports on a comparative study on writing anxiety among English majors who are second language learners. There is little research reporting the level of writing anxiety of second language learners majoring in English. The study examines the relationship between Malaysian and Thailand undergraduates’ writing anxiety and their self-perceived language ability. It also explores the relationship between students’ writing apprehension and their usage frequency of online writing applications. A descriptive research design was adopted in this study. The research measures the students’ level of writing anxiety using adapted Daly-Miller writing apprehension test (1975). The data was collected using questionnaire surveys from a total of 307 English majors of two public universities in Malaysia and one in Thailand. The statistical tests indicated that although the self-perceived proficiency level of the Thai students was significantly lower than the Malaysian students, there was no significant difference among the English majors in their level of writing apprehension. It was also found that there was no statistically significant difference among the students in their usage frequency of most of the online applications. However, only the usage frequency of Instagram was found to be correlated with their apprehension. The study also found no correlation between writing apprehension and the lecturer as the audience of their writing activities. Findings indicate that the technology was widely used by the students for writing. The study indicates that the students were ready to adopt changes in the mode of content delivery from face-to face to online.